2020
DOI: 10.5430/ijhe.v9n3p120
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Traits, Academic Self-Efficacy and Academic Adaptation among University Students in Jordan

Abstract: The current study investigates the relationship between personality traits according to the big five personality factors model, academic self-efficacy and academic adaptation among Hashemite University students in light of gender and specialization. The purposive sample consisted of 546 under graduated students, 258 males and 306 females. Three scales are used: the Five Factor Model (FFM), for academic self-efficacy and for academic adaption. The results show statistically significant differences in the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
(11 reference statements)
2
17
1
Order By: Relevance
“…This is consistent with studies conducted by researchers that personality influences self-efficacy (e.g. Abood et al, 2020;Murugesan & Jayavelu, 2017), achievement motivation (e.g. Diseth & Liartinsen, 2009;Richardson & Abraham, 2009), and job satisfaction (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with studies conducted by researchers that personality influences self-efficacy (e.g. Abood et al, 2020;Murugesan & Jayavelu, 2017), achievement motivation (e.g. Diseth & Liartinsen, 2009;Richardson & Abraham, 2009), and job satisfaction (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The indicators of personality, such as extraversion, agreeableness, conscientiousness, openness to experience, and neuroticism (Costa & McCrae, 1992) if adequate conditions potentially stimulating self-efficacy manifested generality, magnitude, and strength (Bandura, 1994) and then implicate to the job satisfaction manifested work itself, promotion, supervision, and partners/co-workers (Luthan, 2011). The studies carried out by Abood et al (2020), and Murugesan and Jayavelu (2017) indicated that personality affects selfefficacy, while the studies conducted by Bargsted, Ramírez-Vielma, and Yeves (2019), Jurado et al (2019), Machmud (2018), and Park et al (2017) show that self-efficacy affects job satisfaction. Based on argues and studies above, the seventh hypothesis in this study is: H7: Personality had an indirect effect on job satisfaction mediating by self-efficacy.…”
Section: Personality On Job Satisfaction Mediating By Self-efficacymentioning
confidence: 98%
See 2 more Smart Citations
“…(Karada g and Kaya, 2019) revealed that extraversion, openness to experiences and conscientiousness personality traits are directly related with a willingness to the communication of knowledge. (Abood et al, 2020) explored a statistically significant positive correlation between extroversion, openness to experience, academic self-efficacy and academic adaption among university students. While, a negative correlation was observed between neuroticism, conscientiousness, academic self-efficacy and academic adaption.…”
Section: Literature Reviewmentioning
confidence: 99%